Copper‐Mediated Deoxygenative Trifluoromethylation of Benzylic Xanthates: Generation of a CCF3 Bond from an O‐Based Electrophile. Issue 38 (6th August 2013) - Zhu, Lingui; Liu, Shasha; Douglas, Justin T.; Altman, Ryan A.
Abstract The conversion of an alcohol‐based functional group, into a trifluoromethyl analogue is a desirable transformation. However, few methods are capable of converting O‐based electrophiles into trifluoromethanes. The copper‐mediated trifluoromethylation of benzylic xanthates using Umemoto's reagent as the source of CF3 to form CCF3 bonds is described. The method is compatible with an array of benzylic xanthates bearing useful functional groups. A preliminary mechanistic investigation suggests that the CCF3 bond forms by reaction of the substrate with in situ generated CuCF3 and CuOTf. Further evidence suggests that the reaction could proceed via a radical cation intermediate.